2016
DOI: 10.1080/01652176.2016.1155241
|View full text |Cite
|
Sign up to set email alerts
|

Molecular serotyping and antimicrobial resistance profiles ofActinobacillus pleuropneumoniaeisolated from pigs in South Korea

Abstract: Background: Actinobacillus pleuropneumoniae (APP) causes porcine pleuropneumonia (PP). Objective: Serotypes and antimicrobial resistance patterns in APP isolates from pigs in Korea were examined. Methods: Sixty-five APP isolates were genetically serotyped using standard and multiplex PCR (polymerase chain reaction). Antimicrobial susceptibilities were tested using the standardized disk-agar method. PCR was used to detect b-lactam, gentamicin and tetracycline-resistance genes. The random amplified polymorphic D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 27 publications
(49 reference statements)
2
18
0
Order By: Relevance
“…The poor specificity of the detection methods for A. pleuropneumoniae and the rapid progression of the infection frequently prompt widespread application of antibiotic treatment on the mere suspicion of an infection [ 14 ]. This contributes to the overuse of antibiotics, which promotes selection of resistant bacteria and may indirectly lead to the spread of antibiotic resistance genes through the food chain [ 15 , 16 ]. Accordingly, an effective vaccine against A. pleuropneumoniae , which protects across the 16 serovars is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…The poor specificity of the detection methods for A. pleuropneumoniae and the rapid progression of the infection frequently prompt widespread application of antibiotic treatment on the mere suspicion of an infection [ 14 ]. This contributes to the overuse of antibiotics, which promotes selection of resistant bacteria and may indirectly lead to the spread of antibiotic resistance genes through the food chain [ 15 , 16 ]. Accordingly, an effective vaccine against A. pleuropneumoniae , which protects across the 16 serovars is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…The pangenome of six Brazilian APP8 isolates was recently reported (Prado et al, 2020) and showed that the gene repertoire is well conserved in relation to the available genomes of other serovars, though the presence of serovar-specific patterns of AMR within A. pleuropneumoniae is debatable (Asawa et al, 1995;Lee et al, 2015;Kim et al, 2016). Due to a low prevalence of clinical pleuropneumonia caused by APP8 globally, most studies on AMR have been performed on other serovars.…”
Section: Discussionmentioning
confidence: 99%
“…This study used non-probabilistic sampling obtained from data of a private laboratory. One hundred sixty bacterial strains isolated from pigs with clinical respiratory signs from 51 pig farms in Brazil were studied, as follows: P. multocida [78/160 (48.75%) Lönnqvist et al (2018), and Kim et al (2016). The breakpoints used are detailed in the supplementary material.…”
Section: Methodsmentioning
confidence: 99%